Extended Warranty Policies with Warranty Options - Rangan, Alagar; Khiabani, Vahidhossein (IEEE, 2008)
We consider a repairable system subject to two types of failures; minor and major requiring minimal repair and replacement respectively. Extended warranty models for the system that includes a free replacement period and an extended warranty period will be analyzed. Consumers have several warranty options during the extended warranty period. Explicit expressions for the manufacturer's long run average profit per unit time under these options are obtained. We also consider case of demand as a displaced log linear function of the product price, fixed warranty period and the extended warranty period. A numerical illustration is provided to demonstrate optimal product pricing and warranty period.
International Conference on Industrial Engineering and Engineering Management -- DEC 08-11, 2008 -- Singapore, SINGAPORE
Keywords: Extended warranty; types of failure; minimal repair; log linear demand function